Persistence of African Swine Fever Virus in Feed and Feed Mill Environment over Time after Manufacture of Experimentally Inoculated Feed - Grace E. Houston; Jessie D. Trujillo; Cassandra K. Jones; Taeyong Kwon; Charles R. Stark; Konnor R. Cool; Chad B. Paulk; Natasha N. Gaudreault; Jason C. Woodworth; Igor Morozov; Carmina Gallardo; Jordan T. Gebhardt; et al. (Kansas Agricultural Experiment Station Research Reports, 2022)
To reduce the risk of disease from harmful feed-based pathogens, some feed manufacturers quarantine high-risk ingredients prior to their inclusion in feed. Data exist that confirms this practice is effective, but to our knowledge there is no information about porcine pathogen survival in mill environments. The objective of this study was to determine survival of African swine fever virus (ASFV) in swine feed and on mill surfaces after manufacture of experimentally inoculated swine feed. A pilot-scale feed mill was placed within a biosecurity level (BSL) 3 facility to manufacture batches of feed. The priming batch, Batch 1, was ASFV-free feed and was followed with Batch 2 which was experimentally inoculated with ASFV (5.6 × 104TCID50/gram). Four subsequent ASFV-free batches were then manufactured (Batch 3-6). After each batch of feed, 10 feed samples were aseptically collected in a double ‘X’ pattern. During feed manufacturing, 24 steel coupons were placed on the floor of the manufacturing area and feed dust was allowed to settle onto them overnight. Once feed manufacturing was completed, feed samples and steel coupons were stored at room temperature. On the day of (day 0) and d 3, 7, 14, 28, 60, 90, and 180 after feed manufacturing, feed samples and 3 steel coupons were randomly selected, taken out of storage, and analyzed for ASFV DNA. For feed samples there was a statistically significant (P= 0.023) batch × day interaction for log10genomic copies per gram of feed, and a marginal statistical significance (P= 0.072) for batch × day interaction for cycle threshold (Ct) values. This indicates that the batch of feed and days held at room temperature impacted the amount of the detectable ASFV DNA in feed samples. There was no evidence (P= 0.433) of ASFV degradation on environmental coupons over the 180-d storage period. This study found that quarantine time can help reduce, but not eliminate ASFV DNA in feed over time. Surprisingly, ASFV DNA is detectable on feed manufacturing surfaces for at least 180 days.
Keywords: African swine fever virus; dust; feed mill; feed samples; persistence